Alice in Wonderland: Voluntary sector organisations’ experiences of Transforming Rehabilitation: - Corcoran, Mary (Probation journal, 2019)
This article explores the experience of voluntary sector organisations (VSOs) in the Transforming Rehabilitation (TR) experiment. It identifies the motivations, expectations, rationalities and experiences of voluntary sector participants, drawing on interviews conducted with charity directors and community rehabilitation company executives between 2015 and 2017. It concludes by reflecting on the losses and gains that accrued to different parts of the voluntary sector, as well as critically examining the conditions by which ‘winning’ and ‘losing’ were structured within the TR framework.